Uganda : Technical Assistance Report-Report on the National Accounts Statistics Mission. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Assistance Report discusses technical advice and recommendations given by the IMF mission to the authorities of Uganda regarding further development of estimates of quarterly GDP for expenditure components and the development of production accounts for main institutional sectors. Together with local counterpart staff, the IMF mission finalized the Microsoft Excel framework for producing the volume measure of constant price quarterly expenditure GDP. It is recommended that the Uganda Bureau of Statistics (UBOS) undertake a review of the regimes used for compiling the three different estimates of GDP. The UBOS should also carry forward the quarterly expenditure compilation process by developing the basis for a current price equivalent to the constant price Commodity Flow Model.